Data of chemical analysis and electrical properties of SnO2-TiO2 composite nanofibers - Zinab, H. Bakr; Qamar, Wali; Jamil, Ismail; Elumalai, Naveen Kumar; Ashraf, Uddin; Rajan, Jose (Elsevier Inc., 2018)
In this data article, we provide energy dispersive X-ray spectroscopy (EDX) spectra of the electrospun composite (SnO2-TiO2) nanowires with the elemental values measured in atomic and weight%. The linear sweep voltammetry data of composite and its component nanofibers are provided. The data collected in this article is directly related to our research article “Synergistic combination of electronic and electrical properties of SnO2 and TiO2 in a single SnO2-TiO2 composite nanowire for dye-sensitized solar cells”.